Standing in the light : the captive diary of Catherine Carey Logan, Delaware Valley, Pennsylvania, 1763 - Osborne, Mary Pope (Dear America., 1998)
A Quaker girl's diary reflects her experiences growing up in the Delaware River Valley of Pennsylvania and her capture by Lenape Indians in 1763.